From empire to aid: Analysing persistence of colonial legacies in foreign aid to Africa - Swetha Ramachandran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
For decades now, Western development agencies and donors have been castigated for their colonial biases in providing aid to Africa. It is well established that donors provide considerably more foreign aid to their former colonies relative to other countries in the region. However, what happens over time to the influence of the former-colonizer-turned-donor within the aid recipient countries? Does their influence become stronger over time due to early and significant contributions, or does it decline with the emergence of other contemporary donors? Additionally, do these colonial legacies evolve differently depending on who the former colonial power was? Using a statistical analysis of the OECD Creditor Reporting System database, I show that the persistence of colonial legacies in aid, measured through donor concentration, is declining over time across all aid recipient countries. However, the pace of decline varies: former French African colonies, while more concentrated at any given time, see this concentration decrease faster compared with former British African colonies. These trends are influenced by the growing number of donors, France's morphing Françafrique policy, and the ongoing influence of former colonizers through military and trade avenues. By drawing on interdisciplinary approaches, this research attempts to empirically measure persistence of colonial legacies across Africa and help inform policy strategies for reforming aid practices by understanding the broader trends.
Keywords: 330; measuring colonial legacies; foreign aid; donor concentration; Africa